Interplay of Customer Satisfaction, Innovation, and Product Quality: Key Determinants of Company Performance - Restrepo-Morales, Jorge Aníbal; Valencia-Cárdenas, Marisol; López-Cadavid, Diego Alejandro (Journal of technology management & innovation, 2024)
Customer Satisfaction, Innovation, and Product Quality stands as a cornerstone for micro, small, and medium-sized enterprises (MSMEs) seeking growth, competitiveness, and long-term sustainability. This study delves into the intricacies of Customer Satisfaction, Innovation, and Product Quality's influence on MSME performance within the dynamic Iberoamerican business landscape. Adopting a quantitative research approach, we investigate the relationship between Customer Satisfaction, Innovation, and Product Quality and MSME performance across Iberoamerican. A composite index derived from self-reported data was employed to gauge MSME performance, drawing upon a comprehensive survey of 9,300 Iberoamerican MSMEs. Our findings reveal that factors such as company origin, size, and age significantly impact the level of innovation achievable by MSMEs. Notably, younger, medium-sized companies exhibit a proclivity for higher innovation compared to older firms and micro-enterprises. The study's implications for theory and practice extend to policymakers, business owners, and stakeholders invested in fostering MSME growth and development.